Clinicians’ experience on the effectiveness of pharmacotherapy in patients with first-episode depression: a randomized controlled trial based on pharmacogenomics - Tong, Jie; Yuan, Jie; Qin, Yu; Zhu, Na; Zhang, Tingting; Zhu, Xiaochun; Xu, Yuanyuan; Liu, Meilin; Zhang, Jie; Sun, Xirong (Frontiers in Pharmacology, 2025)
BackgroundDue to differences in drug efficacy, the risk of adverse reactions, and individual differences between patients, clinicians face significant challenges in terms of selecting drugs for the treatment of depression. However, no previous studies have compared the efficacy of antidepressant treatments between psychiatrists with different levels of experience based on pharmacogenomics approach.MethodsA total of 178 patients were recruited and randomly assigned to pharmacogenomics-guided treatment group or regular treatment control group. The control group was further divided into the senior doctor and the nonsenior doctor subgroups. All participants completed pharmacogenomic assessments at baseline. They also completed the 17-items Hamilton Depression Scale (HAM-D17), Dimensional Anhedonia Rating Scale (DARS), Perceived Deficits Questionnaire-Depression (PDQ-D), and Antidepressant Side Effect Checklist (ASEC) at baseline and at 4-week, 8-week, 16-week, and 32-week follow-ups. The study protocol was registered with ClinicalTrials.gov (NCT05669391).ResultsCompared with the control group, pharmacogenomics-guided group presented significant differences in DARS and ASEC scores at 32 weeks (PBonferroni< 0.05), with significant time and group effect (P < 0.05). However, there was no significant difference in HAM-D17 and PDQ-D scores between the two groups at 32 weeks (PBonferroni> 0.05). The number of antidepressant changes at 32 weeks in the nonsenior doctor subgroup was significantly higher than that in the senior doctor subgroup (1.04 vs. 0.31, P = 0.005). There was no significant difference in the number of combined antidepressants, the number of patients who used somnifacients, HAM-D17 scores, DARS scores, PDQ-D scores, and ASEC scores between the two groups (P > 0.05). The number of antidepressant changes and HAM-D17 scores are 32-week were negatively correlated with the doctor’s years of work experience (r = −0.25, P = 0.012; r = −0.29, P = 0.004; respectively).ConclusionPharmacogenomics-guided treatment can effectively mitigate the occurrence of anhedonia and side effects in patients with first-episode depression. Higher level of clinical experience among psychiatrists can lead to significant reduction in the frequency of antidepressant drug changes, and the depressive symptoms at the endpoint are negatively correlated with the clinicians’ work experience. Pharmacogenomics may reduce the influence of clinical experience on treatment outcomes in primary mental healthcare settings.